Preparation method of SbCo / Co alloy modified carbon nanotube composite material and application of SbCo / Co alloy modified carbon nanotube composite material in lithium-sulfur battery

The carbon nanotubes modified with SbCo/Co alloy were synthesized by wet method and loaded with elemental sulfur, which solved the problems of poor sulfur conductivity and volume changes in lithium-sulfur batteries, and achieved efficient electrochemical performance improvement, especially in cycle stability and It exhibits excellent results in rate performance.

CN119252923AActive Publication Date: 2025-01-03HIGH & NEW TECH RES CENT OF HENAN ACAD OF SCI +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411376833.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing lithium-sulfur batteries have poor conductivity, volume changes and "shuttle effect" and lead to low sulfur utilization efficiency and rapid attenuation of battery capacity due to the poor conductivity of sulfur element and lithium sulfide. The existing porous material modification methods limit electron conduction efficiency and adsorption balance.

Method used

The carbon nanotubes modified with SbCo/Co alloy were synthesized by wet method, and the chemical substance ratio in the hydrolysis reaction was adjusted to form a SbCo/Co@CNT composite with high conductivity and catalytic properties, and the elemental sulfur was loaded by in-situ pyrolysis, as Lithium sulfur battery positive electrode material to improve performance.

Benefits of technology

Achieve excellent electrochemical performance of SbCo/Co@CNT composites in lithium-sulfur batteries, including good cycle stability and rate performance, capacity retention rate up to 88%, and excellent cycle stability under high current density and capacity maintenance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a SbCo / Co alloy modified carbon nanotube composite material, which comprises the following steps: 1) mixing Co (NO3) 2.6 H2O, polyethylene glycol, antimonide, boric acid, urea and deionized water, stirring the mixture until the mixture is clarified, drying and grinding to obtain precursor powder; and 2) pyrolyzing the precursor powder for 3-8 hours at 800-1000 DEG C in an inert gas atmosphere, thereby obtaining the product. The interaction between Sb and Co elements can effectively improve the physical and chemical properties of a single element, and the obtained SbCo / Co nanoparticles can effectively improve the chemical adsorption effect on polysulfides and effectively catalyze the mutual conversion between the polysulfides. In addition, due to the unique structure of the carbon nanotubes, electron transfer can be further improved, and the carbon nanotubes have rich internal space to load sulfur and buffer volume expansion. After S is loaded, the SbCo / Co-CNT carbon nanotube functional hybrid material shows excellent electrochemical performance, including excellent cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery positive electrode materials, and specifically relates to a preparation method of a SbCo / Co alloy-modified carbon nanotube (SbCo / Co@CNT) composite material and its application in high-performance lithium-sulfur Li-S batteries. Background Art

[0002] With the development of new energy vehicles and mobile electronic devices, humans have put forward higher requirements for energy storage methods. Among the various energy storage methods, lithium-sulfur batteries have a higher theoretical energy density (2600 Wh kg -1 ) has received widespread attention. However, commercial Li-S batteries still face many challenges, such as the poor conductivity of sulfur (S8) and lithium sulfide (Li2S), changes in battery volume during operation, and the "shuttle effect" caused by polysulfides. These factors lead to low sulfur utilization efficiency and rapid battery capacity decay. Solving the above problems is the key to improving the performance of Li-S batteries.

[0003] Among the many solutions, the development of effective porous materials plays an important role in improving the performance of Li-S batteries. Such materials have a certain composition and structure, which can optimize the conductivity of the battery, reduce volume changes and "shuttle effect".

[0004] Traditional porous materials are often made by attaching sulfur to carbon nanospheres, carbon nanotubes and two-dimensional graphene. This strategy can enhance the conductivity of the material and the physical adsorption of polysulfides (LiPSs). However, due to the limited physical adsorption capacity of this type of material, it can only partially improve battery performance. Due to the existence of the above problems, improving the performance of Li-S batteries by modifying the surface structure of porous materials has become a research hotspot in recent years.

[0005] The method of modifying the surface structure of porous materials often combines the adsorption of sulfur on LiPSs with electrochemical catalysis, and attaches the obtained electrical material to the positive electrode of the battery. This strategy can optimize the reaction kinetics of the sulfur positive electrode. Researchers have explored hybrid composite materials attached with metal oxides, metal carbides, metal nitrides, metal phosphides and metal sulfides, which significantly improved the performance of Li-S batteries. However, these materials limit the electronic conduction efficiency of Li-S batteries and affect the adsorption balance of LiPSs on the positive electrode surface. If the adsorption and diffusion balance of LiPSs can be achieved, it is expected to further improve the performance of Li-S batteries. Based on this, the present invention was developed. Summary of the invention

[0006] The present invention aims to overcome the defects of the prior art and provide a method for preparing a SbCo / Co alloy modified carbon nanotube (SbCo / Co@CNT) composite material. The method adjusts the ratio of Co(NO3)2·6H2O, polyethylene glycol (PEG), antimonide and CH4N2O in the hydrolysis reaction, wet-synthesizes the precursor, and obtains a SbCo / Co alloy modified carbon nanotube positive electrode composite material with high conductivity and catalytic performance.

[0007] Another object of the present invention is to provide an application of the SbCo / Co alloy-modified carbon nanotubes prepared by the above method in lithium-sulfur batteries, which are used as sulfur carriers to load elemental sulfur in nanotubes through in-situ pyrolysis to obtain a composite electrode material, which is used as a positive electrode material for lithium-sulfur batteries to improve the performance of lithium-sulfur batteries.

[0008] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a SbCo / Co alloy modified carbon nanotube (SbCo / Co@CNT) composite material comprises the following steps: 1) Mix Co(NO3)2·6H2O, polyethylene glycol (PEG), antimonide, boric acid (H3BO3), urea (CH4N2O) and deionized water, stir vigorously (stir for 10-15 minutes) until the mixture is clear, dry, and grind to obtain a precursor powder; 2) The precursor powder is pyrolyzed at 800-1000℃ for 3-8 h in an inert gas atmosphere (such as argon). 2+ and Sb 3+ By reduction, carbon nanotubes with trace amounts of SbCo / Co alloy nanoparticles attached are obtained.

[0009] Specifically, the antimonide includes but is not limited to one or two of H6KO6Sb, SbCl3, etc.; the molar ratio of Co(NO3)2·6H2O to the antimonide may range from 1 to 10:1.

[0010] Furthermore, the mass ratio of the polyethylene glycol to Co(NO3)2·6H2O may be in the range of 20-40:1. The polyethylene glycol is preferably PEG 2000.

[0011] Furthermore, the mass ratio of the boric acid to Co(NO3)2·6H2O may be in the range of 0-15:1, preferably 5-12:1.

[0012] Furthermore, the mass ratio of urea to Co(NO3)2·6H2O may be 200-500:1, preferably 250-360:1. In step 1), the drying temperature may be 100-200°C.

[0013] The present invention provides a SbCo / Co alloy modified carbon nanotube composite material (SbCo / Co@CNT) prepared by the above method, the diameter of which is 100-150 nm.

[0014] The present invention uses the principle of in-situ reduction pyrolysis to load sulfur on carbon nanotubes attached with trace amounts of SbCo / Co alloy nanoparticles, and then uses the carbon nanotubes as positive electrode materials for lithium-sulfur batteries. Specifically, the present invention also provides the use of the above-mentioned SbCo / Co alloy-modified carbon nanotube composite material in high-performance lithium-sulfur batteries. When used, the SbCo / Co alloy-modified carbon nanotube composite material can be ground and mixed with elemental sulfur in a mass ratio of 1:1-10, and the mixture can be kept warm at 140-170°C for 10-14h in a hydrothermal reactor for reaction. After the reaction is completed and cooled to room temperature, the mixture can be transferred to a tubular furnace and kept warm at 180-220°C for 0.4-1h in an argon atmosphere for heat treatment to remove excess S, thereby obtaining a positive electrode material for a lithium-sulfur battery (SbCo / Co@CNT-S powder), and the positive electrode material for a lithium-sulfur battery can be used to prepare a lithium-sulfur battery.

[0015] The present invention also provides a lithium-sulfur battery positive electrode material, which comprises grinding and mixing the SbCo / Co alloy-modified carbon nanotube composite material and elemental sulfur in a mass ratio of 1:1-10, keeping the mixture at 140-170°C for 10-14h in a hydrothermal kettle, and then transferring the mixture to a tubular furnace and keeping the mixture at 180-220°C for 0.4-1h in an argon atmosphere to obtain the lithium-sulfur battery positive electrode material.

[0016] In the present invention, the interaction between Sb and Co elements can effectively improve the physical and chemical properties of the single element, and the obtained SbCo / Co nanoparticles can effectively improve the chemical adsorption of polysulfides and effectively catalyze the mutual conversion between polysulfides. In addition, due to the unique structure of carbon nanotubes, electron transfer can be further improved, and it has abundant internal space to load sulfur and buffer volume expansion. After loading sulfur, the SbCo / Co@CNT carbon nanotube functional hybrid material exhibits excellent electrochemical properties, including excellent cycle stability and rate performance.

[0017] Compared with existing materials, the present invention has the following advantages and beneficial effects: 1) The present invention loads SbCo / Co alloy nanoparticles inside carbon nanotubes through in-situ pyrolysis to prepare a multilayer hybrid hollow SbCo / Co@CNT composite material with controllable morphology, uniform size and good structural stability; by controlling the addition ratio of Co(NO3)2·6H2O and antimonide, SbCo / Co@CNT and Co@CNT can be prepared using this step.

[0018] 2) After sulfur loading, the multilayer hybrid hollow SbCo / Co@CNT nanotube composite material prepared by the present invention has excellent electrochemical performance as a positive electrode material for Li-S batteries due to its excellent multilayer absorption and protection, including good cycle stability and high reversible specific capacity. The SbCo / Co@CNT functional composite material prepared by the present invention exhibits excellent electrochemical performance. At a current density of 1C, the SbCo / Co@CNT functional composite material prepared by the present invention also exhibits very excellent rate performance, and at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C, it exhibits 1416 mAh g -1 , 1204 mAh g -1 、1033 mAh g -1 , 922 mAh g -1 and 658 mAh g -1 When the current density is restored to 0.1C, its specific capacity is still as high as 1247 mAh g -1 The capacity retention rate is 88%. Similarly, after 100 cycles of charge and discharge at a current density of 0.1C, its specific capacity is still as high as 1096.5 mAh g -1 , which is much higher than other materials reported in the literature (Co@CNT: 772.6 mAh g -1 ; CNT: 627.0 mAh g -1 ); at a high current density of 1C, the charge-discharge capacity of the SbCo / Co@CNT functional composite material prepared by the present invention is still as high as 1020.2 mAh g -1 After 500 charge and discharge cycles, the charge and discharge capacity remained at 948.7mAh g⁻¹, with an average decay of only 0.014% per cycle, demonstrating extremely excellent cycle stability.

[0019] 3) The multilayer hybrid hollow SbCo / Co@CNT nanotube composite material prepared by the preparation method of the present invention has broad application prospects in high-performance Li-S batteries and can be further applied to related electronic device fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a low-magnification SEM image of the SbCo / Co@CNT prepared in Example 1; Figure 2 This is a high magnification SEM image of the SbCo / Co@CNT prepared in Example 1; Figure 3 This is the XPS graph of SbCo / Co@CNT prepared in Example 1; Figure 4 Cyclic charge-discharge diagrams of the three materials at different rates of 0.1C, 0.2C, 0.5C, 1C, and 2C, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, and CNT-S; Figure 5 shows the long-life cycle discharge times of the three materials under 1 C charge and discharge conditions, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, CNT-S; Figure 6 shows the specific capacity of the three materials after 100 cycles under 0.1 C charge and discharge conditions, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, and CNT-S. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0022] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared by conventional methods in the art.

[0023] Room temperature refers to 25±5°C.

[0024] Example 1 The preparation of SbCo / Co@CNT specifically includes the following steps: 34.2 mg of Co(NO3)2·6H2O and 30.8 mg of H6KO6Sb (the molar ratio of Co(NO3)2·6H2O to H6KO6Sb was 1:1, both were 0.117 mmol) were added to 150 mL of deionized water containing 11 g of urea, 0.3 g of boric acid and 1 g of PEG-2000, and the mixture was vigorously stirred until clear; the above solution was evaporated to dryness at 100°C; after grinding the above solid, it was heated to 900°C at a heating rate of 5°C / min under argon atmosphere and pyrolyzed for 5 h to obtain SbCo / Co@CNT.

[0025] The SEM image of the prepared SbCo / Co@CNT is shown in Figure 1 and 2 As shown. Figure 1 and 2 It can be seen that SbCo / Co@CNT is a nanotube of uniform size, with a diameter of about 100-150 nm.

[0026] Figure 3 The XPS graph of SbCo / Co@CNT prepared in this example is given; according to the analysis of the characteristic peaks in the graph, it can be known that the material is composed of carbon, cobalt, nitrogen and antimony elements.

[0027] The preparation of SbCo / Co@CNT loaded sulfur specifically includes the following steps: Take 0.1 g of the prepared SbCo / Co@CNT, mix it with 0.4 g of sulfur powder and grind it evenly; heat the mixture to 156°C in a hydrothermal reactor and keep it warm for 12 h. After the reaction, cool it to room temperature; transfer the mixture to a tube furnace and heat it again to 200°C in an argon atmosphere for pyrolysis for 1 h (heating rate 2°C / min) to obtain SbCo / Co@CNT-S positive electrode material.

[0028] The prepared SbCo / Co@CNT-S positive electrode material was evenly mixed with a conductive agent (Super-P) and a binder (PVDF) in a mass ratio of 7:2:1, N-methylpyrrolidone (NMP) was added and stirred, and then coated on an aluminum foil to make an electrode sheet, which was dried in a vacuum oven for 12 hours.

[0029] In an argon atmosphere glove box, the above electrode sheet was used as the positive electrode and the metal lithium sheet was used as the negative electrode. A DME-DOL (volume ratio 1:1) mixture containing 1M LiTFSI and 2 wt% LiNO3 was used as the electrolyte to assemble the 2032 button cell and then test it. The test conditions were: charge and discharge current density of 0.1C, 0.2C, 0.5C, 1C, 2C (1C = 1675mA / g), and the charge and discharge cut-off voltage was 1.7-2.8V. The cycle number-specific capacity performance curve obtained from the test is shown in the figure below: Figure 4-6 as shown in .

[0030] Comparative Example 1 The preparation of Co@CNT specifically includes the following steps: 65 mg of Co(NO3)2·6H2O was added to 150 mL of deionized water containing 11 g of urea, 0.3 g of boric acid and 1 g of PEG-2000, and the mixture was vigorously stirred until clear; the above solution was evaporated to dryness at 100°C; after grinding the above solid, it was heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and pyrolyzed for 5 h to obtain Co@CNT.

[0031] The preparation of Co@CNT loaded sulfur specifically includes the following steps: Take 0.1 g of the prepared Co@CNT, mix it with 0.4 g of sulfur powder and grind it evenly; heat the mixture to 156°C in a hydrothermal reactor and keep it warm for 12 h, and cool it to room temperature after the reaction ends; transfer the mixture to a tubular furnace and heat it again to 200°C in an argon atmosphere for pyrolysis for 1 h (heating rate 2°C / min) to obtain Co@CNT-S positive electrode material.

[0032] The prepared Co@CNT-S positive electrode material was evenly mixed with a conductive agent (Super-P) and a binder (PVDF) in a mass ratio of 7:2:1, N-methylpyrrolidone NMP was added, stirred, and then coated on an aluminum foil to make an electrode sheet, which was dried in a vacuum oven for 12 hours.

[0033] In an argon atmosphere glove box, the above electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, and a DME-DOL (volume ratio 1:1) mixed solution containing 1M LiTFSI and 2 wt% LiNO3 was used as the electrolyte to assemble a 2032 button cell, and then tested. The test conditions were: charge and discharge current density of 0.1C, 0.2C, 0.5C, 1C, 2C (1C = 1675mA / g), and the charge and discharge cut-off voltage was 1.7-2.8V. The cycle number-specific capacity performance curve obtained from the test is shown in the figure below. Figure 6 After 100 cycles of charge and discharge at a current density of 0.1C, the specific capacity is 772.6 mAh g -1 .

[0034] Comparative Example 2 The preparation of CNT specifically includes the following steps: 0.3 g of boric acid, 11 g of urea and 1 g of PEG-2000 were added to 150 mL of deionized water, and the mixture was vigorously stirred until clear; the above solution was evaporated to dryness at 100°C; after the above solid was ground, it was heated to 900°C at a heating rate of 5°C / min under an argon atmosphere and pyrolyzed for 5 h to obtain CNTs.

[0035] The preparation of CNT-loaded sulfur specifically includes the following steps: Take 0.1 g of the prepared CNT, mix it with 0.4 g of sulfur powder and grind it evenly; heat the mixture to 156°C in a hydrothermal reactor and keep it warm for 12 h, and cool it to room temperature after the reaction ends; transfer the mixture to a tubular furnace and heat it again to 200°C in an argon atmosphere for pyrolysis for 1 h (heating rate 2°C / min) to obtain CNT-S positive electrode material.

[0036] The prepared CNT-S positive electrode material was evenly mixed with a conductive agent (Super-P) and a binder (PVDF) in a mass ratio of 7:2:1, N-methylpyrrolidone NMP was added, stirred, and then coated on an aluminum foil to make an electrode sheet, which was dried in a vacuum oven for 12 hours.

[0037] In an argon atmosphere glove box, the above electrode sheet was used as the positive electrode and the metal lithium sheet was used as the negative electrode. A DME-DOL (volume ratio 1:1) mixture containing 1M LiTFSI and 2 wt% LiNO3 was used as the electrolyte to assemble the 2032 button cell and then test it. The test conditions were: charge and discharge current density of 0.1C, 0.2C, 0.5C, 1C, 2C (1C = 1675mA / g), and the charge and discharge cut-off voltage was 1.7-2.8V. The cycle number-specific capacity performance curve obtained from the test is shown in the figure below: Figure 6 After 100 cycles of charge and discharge at a current density of 0.1C, the specific capacity is 627.0 mAh g -1 .

[0038] Figure 4 The cyclic charge and discharge diagrams of the three materials at different rates are given, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, and CNT-S. Figure 4 It can be seen that at a current density of 1C, the SbCo / Co@CNT functional composite material also exhibited excellent rate performance, showing 1416 mAhg at current densities of 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively. -1 , 1204 mA g -1 、1033 mAh g -1 , 922 mAh g -1 and 658 mAh g -1 When the current density is restored to 0.1C, its specific capacity is still as high as 1247 mAh g -1 The capacity retention rate was 88%. Co@CNT exhibited 1099.5 mAh g at current densities of 0.1 C, 0.2 C, 0.5 C, 1C, and 2C, respectively. -1 , 916.1 mAh g -1 、736.7 mAh g -1 、579.4 mAhg -1 、389.5 mAh g -1 When the current density is restored to 0.1C, the specific capacity is 955.6 mAh g -1 The CNTs exhibited a capacity of 932.3 mAh g at current densities of 0.1 C, 0.2 C, 0.5 C, 1 C, and 2 C, respectively.-1 、733.2 mAh g -1 、553.2 mAh g -1 , 432.5 mAh g -1 , 246.1 mAh g -1 When the current density is restored to 0.1C, the specific capacity is 762.8 mAh g -1 .

[0039] Figure 5 shows the long-life cycle discharge times of the three materials at 1 C, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, and CNT-S. Figure 5 It can be seen that at a high current density of 1C, the charge and discharge capacity of the SbCo / Co@CNT functional composite material is still as high as 1020.2 mAh g -1 After 500 charge-discharge cycles, the charge-discharge capacity remained at 948.7 mAh g -1 The average decay rate per cycle is only 0.014%, showing an extremely excellent cycle life. Under 1C conditions, the charge and discharge capacities of Co@CNT and CNT after 500 long cycles are only 614.4 mAh g -1 、CNT 354.5 mAh g -1 .

[0040] Figure 6 shows the specific capacity of the three materials after 100 cycles of charge and discharge at 0.1 C, from top to bottom: SbCo / Co@CNT-S, Co@CNT-S, CNT-S. The SbCo / Co@CNT functional composite material exhibits excellent electrochemical performance. After 100 cycles of charge and discharge at a current density of 0.1 C, its specific capacity is still as high as 1096.5 mAh g -1 , which is much higher than other materials reported in the literature (Co@CNT: 772.6 mAh g -1 、CNT:627.0 mAh g -1 ),See Figure 6 .

[0041] Example 2 The preparation of SbCo / Co@CNT, which differs from Example 1 in that H6KO6Sb is replaced by SbCl3, specifically includes the following steps: 36.4 mg of Co(NO3)2·6H2O and 28.6 mg of SbCl3 (the molar ratio of Co(NO3)2·6H2O to SbCl3 was 1:1, both were 0.125 mmol) were added to 150 mL of deionized water containing 11 g of urea, 0.3 g of boric acid and 1 g of PEG-2000, and the mixture was vigorously stirred until clear; the above solution was evaporated to dryness at 100°C; after grinding the above solid, it was heated to 900°C at a heating rate of 5°C / min under argon atmosphere and pyrolyzed for 5 h to obtain SbCo / Co@CNT.

[0042] The preparation of SbCo / Co@CNT loaded sulfur specifically includes the following steps: Take 0.1 g of the prepared SbCo / Co@CNT, mix it with 0.4 g of sulfur powder and grind it evenly; heat the mixture to 156°C in a hydrothermal reactor and keep it warm for 12 h. After the reaction, cool it to room temperature; transfer the mixture to a tube furnace and heat it again to 200°C in an argon atmosphere for pyrolysis for 1 h (heating rate 2°C / min) to obtain SbCo / Co@CNT-S positive electrode material.

[0043] The prepared SbCo / Co@CNT-S cathode material was made into an electrode sheet according to the method of Example 1, and assembled into a button cell, and the electrochemical performance test was carried out under the same conditions. The results showed that its performance was equivalent to that of Example 1.

[0044] In summary, after sulfur loading, the multilayer hybrid hollow SbCo / Co@CNT nanotube composite material prepared by the present invention has excellent multilayer absorption and protection effects, which enables it to exhibit excellent electrochemical properties as a positive electrode material for Li-S batteries, including good cycle stability and high reversible specific capacity.

Claims

1. A method for preparing a SbCo / Co alloy modified carbon nanotube composite material, characterized in that: The steps include: 1) Co(NO3)2·6H2O, polyethylene glycol, antimonide, boric acid, urea and deionized water are mixed, the mixture is stirred until clear, dried and ground to obtain a precursor powder; 2) The precursor powder is pyrolyzed at 800-1000°C for 3-8 h in an inert gas atmosphere to obtain the product.

2. The method for preparing the SbCo / Co alloy modified carbon nanotube composite material according to claim 1, characterized in that: The antimonide is one or two of H6KO6Sb and SbCl3; the molar ratio of Co(NO3)2·6H2O to the antimonide is in the range of 1-10:

1.

3. The method for preparing the SbCo / Co alloy modified carbon nanotube composite material according to claim 1, characterized in that: The mass ratio of the polyethylene glycol to Co(NO3)2·6H2O is in the range of 20-40:

1.

4. The method for preparing the SbCo / Co alloy modified carbon nanotube composite material according to claim 1, characterized in that: The mass ratio of the boric acid to Co(NO3)2·6H2O ranges from 0 to 15:

1.

5. The method for preparing the SbCo / Co alloy modified carbon nanotube composite material according to claim 1, characterized in that: The mass ratio of the urea to Co(NO3)2·6H2O is in the range of 200-500:

1.

6. The method for preparing the SbCo / Co alloy modified carbon nanotube composite material according to claim 1, characterized in that: In step 1), the drying temperature is 100-200°C.

7. A SbCo / Co alloy-modified carbon nanotube composite material prepared by the method according to any one of claims 1 to 6.

8. Use of the SbCo / Co alloy-modified carbon nanotube composite material according to claim 7 in lithium-sulfur batteries.

9. The use of the SbCo / Co alloy modified carbon nanotube composite material in a lithium-sulfur battery as claimed in claim 8, characterized in that: The SbCo / Co alloy modified carbon nanotube composite material and elemental sulfur are mixed at a mass ratio of 1:1-10, kept at 140-170°C for 10-14h, and then transferred to a tubular furnace and kept at 180-220°C for 0.4-1h in an argon atmosphere to obtain a lithium-sulfur battery positive electrode material.

10. A positive electrode material for a lithium-sulfur battery, characterized in that: The SbCo / Co alloy modified carbon nanotube composite material according to claim 7 is mixed with elemental sulfur in a mass ratio of 1:1-10, and kept at 140-170°C for 10-14h, and then transferred to a tubular furnace and kept at 180-220°C for 0.4-1h in an argon atmosphere to obtain the product.

Citation Information

Patent Citations

  • Lithium-sulfur battery anode material comprising porous metal and preparation method thereof

    CN102723470A

  • N-doped CNT in-situ coated Co nanoparticle composite material and preparation and application thereof

    CN110311111A

  • Antimonous oxide-carbon nanotube composite material as well as preparation and application thereof

    CN111710532A

  • Carbon nanotube-in-tube@antimony sulfide / antimony composite material and preparation method and application thereof

    CN113659121A